Início da docência: desafios vivenciados pelos professores egressos das licenciaturas da UNIFAL-MG - Tomaz, Ana Caroline De Brito Evangelista (2021)
This dissertation is located around issues that are related to the beginning of the teaching profession and its impasses. To help us weave this work, we use as theoretical references authors who work with the themes "Beginning Teacher", "Teacher Professional Development" and "Initial and Continuing Teacher Training". They are: João Formosinho; Maurice Tardif; Maria Assunção Flores; MichaëlHuberman; among other authors relevant to the research. Some questions guided the discussion, such as: knowing the challenges experienced by teachers in early career, what are the mechanisms of overcoming elaborated by teachers in the face of the challenges experienced in early career and what the teachers' perception of the initial and continuing education process are. In this sense, the work's central objective is to identify the challenges experienced by teachers who graduated from bachelor's courses at UNIFAL-MG and also to verify how initial and/or continuing education contributes to coping with such challenges. The methodology used is qualitative in nature, with a perspective on constructive interpretation, whose data were obtained through the analysis of a questionnaire made available to graduates. According to the construction of meaning nuclei, we performed the analyses and interpretation of the data, noting that the teaching work resists the oppressive forces faced by educators, especially challenging issues that are related not only to teaching, but also to the very construction of the teacher's identity. These challenges are experienced especially by the beginning teacher, whose beginning of the career is often marked by lack of support, either from colleagues or from the institution's own management, often causing him to give up his career or go to work as possible. This brings us to a term widely used in what refers to the beginning of the teaching career that is "survival" in the profession. This term is linked to what we call surviving the first years of the career, because it is during this period that teachers find it more difficult to face the challenges of teaching. We conclude, therefore, that the professional development of teachers depends not only on external factors, such as the initial training of teachers, but also on issues related to the very dynamics of the institution in which it works, especially on the educational system as a whole. That is, one should think more about this professional teacher beginning, so that he finds subsidies, either within the institutions or through public policies, which can help him not only at the beginning of the teaching activity, but also throughout his career as a teacher.